Enhancing Governance in Highway Construction Policies in Vietnam - Nguyen Thi Thuy Ngan; Roni Ekha Putera; Indah Adi Putri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
Efficient highway infrastructure is indispensable for Vietnam's continued economic growth and development. However, the governance of highway construction projects in the country has grappled with numerous challenges that hinder their effective implementation. This study aims to conduct a comprehensive evaluation of the current policies and practices governing highway construction in Vietnam, and propose pragmatic recommendations to enhance the governance framework. A qualitative research approach was employed, involving an in-depth analysis of relevant policy documents and semi-structured interviews with key stakeholders from both the public and private sectors. The findings reveal significant inadequacies in the policy formulation process, a lack of transparency and public participation, as well as ineffective monitoring and accountability mechanisms. To address these critical governance deficits, the study recommends strengthening the legal and regulatory frameworks, improving inter-agency coordination and delineation of responsibilities, actively promoting public-private partnerships, and implementing robust monitoring, evaluation, and audit systems. By instituting these crucial governance reforms, Vietnam can optimize the allocation of resources, enhance the quality of highway construction projects, mitigate risks, and ultimately foster the sustainable development of its vital highway infrastructure network.